External Task Environmental Factors and Competitive Advantage in Retail Pharmacies in Nairobi County, Kenya - Kinuthia, Faith Mumbi; Muchara, Maina; Kihara, Allan (Journal of Business and Strategic Management, 2025)
Purpose: The purpose of this research was to determine the influence of external task environmental factors on competitive advantage in retail pharmacies in Nairobi. Methodology: The study was grounded on the Technology, Organization, and Environment (TOE) framework and adopted post-positivism as the research philosophy. A quantitative approach was used, and primary data were collected through a structured, digitally administered questionnaire. The study targeted 365 registered retail pharmacies that had more than one branch. Stratified random sampling was used to select a sample of 170 pharmacies, and a total of 162 valid responses were received, resulting in a 95% response rate. Data analysis was conducted using Spearman’s rank correlation, chi-square tests, and ordinal logistic regression. Findings: The study established no significant relationship between environmental factors and competitive advantage across all statistical tests. The study concluded that while environmental task factors did not show consistent or significant influence on competitive advantage, individual-level factors, such as innovativeness and IT knowledge played a decisive role. Unique Contribution to Theory, Practice and Policy: The study recommends future research on other actors in the pharmaceutical value chain, including distributors and manufacturers, to expand understanding of e-commerce impact. It also recommends further investigation into cultural dimensions using alternative approaches. The findings are expected to support evidence-based decision making for pharmacy owners, digital transformation policymakers, and stakeholders advancing Kenya’s Vision 2030, the Bottom-Up Economic Transformation Agenda (BETA), and the Sustainable Development Goals (SDGs).